The role of nitric oxide in the reversal of hemorrhagic shock by oxotremorine - AKICI, AHMET; KARAALP, ATİLA; GÜLHAN, REZZAN (My University, 2001)
In the present study, the effect of the nitric oxide synthase inhibitor, N(G)-nitro-L-arginine methylester (L-NAME), on the antishock actions of oxotremorine was investigated in rats subjected to hemorrhagic shock under urethane anesthesia. L-citrulline production in the AV3V region, as an indicator of nitric oxide (NO) synthesis, was assayed by high-performance liquid chromatography (HPLC) with fluorescent detection throughout the experiment. The rats were pretreated with either intravenous (i.v.) physiological saline or L-NAME (2.5 mg/kg) before bleeding. L-NAME potentiated the reversal of hypotension by oxotremorine (25 microg/kg, i.v.). However, oxotremorine either alone or in combination with L-NAME did not produce any significant change in 60-min survival rate at this low dose. Analysis of microdialysis samples collected from the AV3V region showed that L-citrulline concentration increased during bleeding and that this increase was abolished by L-NAME pretreatment. These results may suggest that nitric oxide production contributes to hypotension in rats bled to shock since nitric oxide levels in the AV3V region increased in response to bleeding and nitric oxide synthase (NOS) inhibition abolished this increase and potentiated the oxotremorine-induced reversal of hypotension.
Keywords: Female; Animals; Male; Rats; Blood Pressure; Time Factors; Nitric Oxide; Rats, Sprague-Dawley; Survival Rate; Nitric Oxide Synthase; Cerebral Ventricles; Enzyme Inhibitors; NG-Nitroarginine Methyl Ester; Shock, Hemorrhagic; Oxotremorine; Citrulline